Seismic retrofitting of RC frames with RC infilling (SERFIN Project) - Poljanšek, Martin; Taucer, Fabio; Molina Ruiz, Javier; Chrysostomou, Christis; Kyriakides, Nicholas; Onoufriou, Toula; Roussis, Panayiotis C.; Kotronis, Panagiotis; Panagiotakos, Telemachos; Kosmopoulos, Antonis (My University, 2014)
The effectiveness of seismic retrofitting of multi-storey multi-bay RC-frame buildings by converting selected bays into new walls through infilling with reinforced concrete (RC) was studied experimentally at the ELSA facility of the Joint Research Centre in Ispra (Italy). A fullscale model was tested with the pseudo-dynamic method and consisted of two four-storey (12m tall) three-bay (8.5 m long) parallel frames linked through 0.15 m slabs with the central bay (2.5 m) infilled with a RC wall. The frames were designed and detailed for gravity loads only and are typical of similar frames built in Cyprus in the 1970’s.
Keywords: Reinforced Concrete Frame; Seismic Retrofitting; Infill Walls; Experimental Analysis; Numerical Simulations; Pseudo Dynamic Tests; PsD